Pengaruh Implementasi Knowledge Management Terhadap Kinerja Organisasi Melalui Inovasi Sebagai Variabel Intervening (Studi Kasus Pada UMKM Industri Kreatif Digital di Kota Semarang) - Alifia Saraswati; Widiartanto Widiartanto (Universitas Diponegoro, 2016)
Ministry of Communication and Information Technology currently is creating and developingnew program which is called A Movement of 1000 Digital Startups in Indonesia. Semarang, as one ofcapital cities in Indonesia is also developing its digital creative industry. To develop it, government ofSemarang city needs valid data about innovations and performances in digital creative industry. Tocreate innovation dan develop it, one of the ways is to implementing knowledge management, its stagesform knowledge creation, knowledge sharing, and knowledge implementing. This research aims tounderstand how knowledge management impelementation influencing organizational performancethrough innovation in digital creative industries in Semarang partially and simultaneously. The dataused is primary data, by giving questionnaire to the leaders of MSME’s enterprises, which is 33respondents, determined by total sampling technique because micro, small, and medium’s enterprises ofdigital creative insdustry in Semarang is having a very little amount.The result of this research is implementation of knowledge management is influencinginnovation in large amount, but in organizational performance, it is influencing in few amount. Besides,innovation is not influencing organizational performance, therefore with innovation as interveningvariable cause there is no influence of knowledge management implementation on organizationalperformance in Semarang, it is becaused digital creative industries in Semarang city is still yet matureand still have a priority in innovation, but they don’t have long-term goals to develop theirorganizational performance.